问题 解答题
怎样简便就怎样算.
3
4
×
8
15
÷
8
9
(
2
3
-
1
9
5
26
2
9
÷[(1-
3
7
5
6
]
9
5
+
11
12
+
1
12
+
1
5
3
5
÷6+
1
6
×
2
5
(
2
3
+
1
4
-
1
6
)×12
答案

(1)
3
4
×
8
15
÷
8
9
=
3
4
×
8
15
×
9
8

=

9
20

(2)(

2
3
-
1
9
5
26

=

5
9
×
26
5

=

26
9

(3)

2
9
÷[(1-
3
7
5
6
],

=

2
9
÷[
4
7
×
5
6
],

=

2
9
×
21
10

=

7
15

(4)

9
5
+
11
12
+
1
12
+
1
5

=(

9
5
++
1
5
)+(
11
12
+
1
12
),

=2+1,

=3;

(5)

3
5
÷6+
1
6
×
2
5

=

3
5
×
1
6
+
1
6
×
2
5

=(

3
5
+
2
5
)×
1
6

=

1
6

(6)(

2
3
+
1
4
-
1
6
)×12,

=

2
3
×12+
1
4
×12
-
1
6
×12

=8+3-2,

=9.

判断题
多项选择题